Being born small for gestational age (SGA) might be associated with a higher reoperation rate in proximal hypospadias. Issue 5 (October 2022) - Haid, Bernhard; Tack, Lloyd J.W.; Spinoit, Anne-Françoise; Weigl, Chiara; Steinkellner, Lukas; Gernhold, Christa; Banuelos, Beatriz; Sforza, Simone; O'Kelly, Fardod; Oswald, Josef
Extended Summary: Purpose: Being born small for gestational age (SGA) is associated with a higher frequency and more severe forms of hypospadias as well as with potential developmental differences. This study aims to characterize operative outcomes in SGA boys compared to boys born with normal weight and length for gestational age (appropriate/large for gestational age, AGA/LGA). Methods: Demographic data, hypospadias characteristics, associated pathologies and operative outcomes of boys who underwent hypospadias repair at a single center (10/2012–10/2019) were evaluated. Boys were categorized into SGA and non-SGA, which were then compared using unpaired t-tests and chi square tests. To examine the effect of SGA on reoperative risk, a logistic regression model was applied integrating surgical technique, meatal localization and complex hypospadias (narrow glans/plate, curvature, micropenis, bilateral cryptorchidism). Results: SGA boys accounted for 13.7% (n = 80) of the total cohort (n = 584) and 33% of all proximal hypospadias (n = 99, SGA vs. non-SGA 41.3% vs. 13%, p < 0.001). After a mean follow-up of 18.6 months the reoperation rate for all hypospadias was 17.9% (n = 105). In distal hypospadias there was no difference in reoperation rate between SGA and AGA/LGA boys (p = 0.548, multivariate regression model). For each meatal localization in proximal hypospadias SGA was a significant, independent factor predicting higher reoperation rates (p = 0.019, OR 3.21) in a logistic regression model (Figure ROC). Discussion: Hypospadias surgery carries a substantial risk for unplanned reinterventions. Apart from meatal localization, there are only a few factors (urethral plate quality, glandular diameter, curvature) reported in literature to be associated with reoperative risk. Intrauterine growth retardation associated with SGA might lead to not only a higher probability of proximal hypospadias but also contribute to a higher risk for complications mediated by developmental differences. Whether these findings could help to tailor surgical strategies or adjuvant measures, as for example the application of preoperative hormonal stimulation remains to be determined in future studies. This study is limited by being a single-center series with limited follow-up resulting in some complications probably not yet detected – however, in the same extent in both groups. Conclusion: Based on this study, 33% of all proximal hypospadias cases occur in boys born SGA. While the reoperation rate in boys with distal hypospadias was not influenced by SGA status, SGA proved to be an independent predictor of a higher risk of reoperation in those with proximal hypospadias. After validation of these findings in other centers, this could be integrated into counseling and risk-stratification. Summary Figure ROC Curve for the influence of SGA on the reoperation rate of proximal hypospadias in a multivariate analysis controlling for meatal localization, complex hypospadias, surgical technique and androgen pretreatment. Summary Figure